Whole saliva in X-linked hypohidrotic ectodermal dysplasia - MICHALA ORON LEXNER, ALLAN BARDOW, JENS MICHAEL HERTZ, LIS ALMER, BIRGITTE NAUNTOFTE, & SVEN KREIBOR (IAPD and Blackwell, 2007)
X-linked hypohidrotic ectodermal dysplasia (HED) is the most common type of ectodermal dysplasia. Identification of female carriers of X-linked HED can be difficult because of varying degrees of clinical symptoms due to the X-chromosome inactivation. This is the first study about whole saliva flow and composition in males affected by HED and female carriers all confirmed by molecular genetic analysis.